Bi-Doped SnO Nanosheets Supported on Cu Foam for Electrochemical Reduction of CO2 to HCOOH - An, Xiaowei; Li, Shasha; Yoshida, Akihiro; Yu, Tao; Wang, Zhongde; Hao, Xiaogang; Abudula, Abuliti; Guan, Guoqing (ACS applied materials & interfaces, 2019)
Design and fabrication of efficient electrocatalysts is essential for electrochemical reduction of carbon dioxide (CO2). In this work, bismuth (Bi)-doped SnO nanosheets were grown on copper foam (Bi-SnO/Cu foam) by a one-step hydrothermal reaction method and applied for the electrochemical reduction of CO2 to formic acid (HCOOH). The experimental results indicated that Bi doping stabilized the divalent tin (Sn2+) existing on the surface of the electrocatalyst, making it difficult to be reduced to metallic tin (Sn0) during the electrochemical reduction process. In addition, combining with density functional theory (DFT) calculations, it is found that Bi doping and electron transfer from the catalyst to the Cu foam substrate could enhance the adsorption of *OOCH intermediates. As such, the Bi-doped SnO electrocatalyst exhibited a superior faradaic efficiency of 93% at −1.7 V (vs Ag/AgCl) for the reduction of CO2 to HCOOH, together with a current density of 12 mA cm–2 and excellent stability in at least 30 h of operation.